Insulin resistance and acute glucose changes determine arterial elastic properties and coronary flow reserve in dysglycaemic and first-degree relatives of diabetic patients. Issue 2 (August 2015) - Ikonomidis, Ignatios; Lambadiari, Vaia; Pavlidis, George; Koukoulis, Charalambos; Kousathana, Fotini; Varoudi, Maria; Spanoudi, Filio; Maratou, Eirini; Parissis, John; Triantafyllidi, Helen; Paraskevaidis, Ioannis; Dimitriadis, George; et al.
Abstract: Background: Insulin resistance is linked to endothelial dysfunction. We investigated whether first-degree relatives of type-2 diabetes patients (FDR) present differences in vascular function at baseline and during postprandial hyperglycemia compared to dysglycaemic or normoglycaemic subjects. Methods: We studied 40 FDR with normal oral glucose test (OGTT), 40 subjects with abnormal OGTT (dysglycaemic) and 20 subjects with normal OGTT without parental history of diabetes (normoglycaemic) with similar clinical characteristics. Glucose, insulin, pulse wave velocity (PWV), central systolic blood pressure (cSBP) and augmentation index (AI) were measured at 0, 30, 60, 90 and 120min during OGTT. Coronary flow reserve (CFR) was assessed using Doppler echocardiography at 0 and 120min after OGTT. Insulin sensitivity was evaluated using Matsuda and insulin sensitivity index (ISI). Results: FDR and dysglycaemics had higher fasting insulin, reduced ISI, Matsuda index as well as reduced CFR (2.54 ± 0.5 vs. 2.45 ± 0.3 vs. 2.74 ± 0.5), increased PWV, (8.9 ± 1.1 vs. 10.3 ± 2.4vs. 8.0 ± 1.5 m/sec), AI (23.8 ± 13.6 vs. 26.5 ± 14.4vs.17.7 ± 14%) and cSBP than normoglycaemics (p < 0.05 for all comparisons). During OGTT, AI was similarly reduced in both normoglycaemic and FDR (p < 0.05) at peak insulin levels (60 min) though FDR had 2-fold higher insulin than normoglycaemics. AI was increased in dysglycaemics after peak glucose levels, at 120 min (p < 0.05). CFR was reduced by 10% and 15% at 120min in FDR and dysglycaemic respectively, while remained unchanged in normoglycaemics (p < 0.05). The percent reduction of CFR was related with the percent increase of glucose levels, ISI and Matsuda index(p < 0.05). Conclusion: First-degree relatives and dysglycaemic patients have impaired arterial and coronary microcirculatory function. Insulin resistance determines acute vascular responses during postprandial hyperglycemia. ClinicalTrials.gov Identifier: NCT02244736 . Highlights: We compared first-degree relatives of diabetics with dysglycaemic and normoglycaemics. First-degree relatives had similar level of insulin resistance with dysglycaemics. First-degree relatives and dysglycaemics had impaired arterial elasticity and coronary flow reserve. Insulin resistance was associated with arterial stiffness and coronary flow reserve. During oral glucose test first-degree relatives reduced their coronary flow reserve.